PENENTUAN INDEKS BIAS PANDU GELOMBANG BAHAN SILIKON BENTUK SEGIEMPAT DENGAN METODA DEKOMPOSISI SINUS (*) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
DETERMINATION OF THE REFRACTIVE INDEX OF SILICON RECTANGULAR WAVEGUIDE BY THE SINUSOIDAL DECOMPOSITION METHOD. The effectif index of rectangular silicon waveguide has been computed by sinusoidal decomposition method. The light field can be presented by a scalar wave equation into real matrix equation. The eigenvalue give a guided index effectif and the eigenfunction associated with a wave amplitude. The numerical results depend on the matrix dimension taken and gives us the results in a good agreement with those either the finite element or the effectif index methods